(In)visibility of Professional Practices on Nursing Observation Chart: A Questionnaire Study of Nurse Views - Yıldız Erdat; Süheyla Abaan (Sağlık ve Hemşirelik Yönetimi Dergisi)
Introduction: The Nurse Observation Chart is a form that is used to record daily care practices provided to the patient within 24 hours and collect and monitor patient-related data such as general condition, physiological parameters, laboratory results, fluids, and special needs. Aim: This study aimed to determine the nurses' views regarding the nursing observation chart and the visibility of nursing practices in this form. Method: The descriptive study was conducted with 218 nurses working in Ankara. The data were collected between January 1, 2019, and March 30, 2019, using the Demographic Data Form and the Visibility of Professional Practices Form. Results: 46.8% of nurses thought that the Nurse Observation Chart covered all practices performed in the unit in which they served, and 48.6% of nurses thought that their professional practices were completely visible in the nursing records. The first three practices that nurses stated that they 'always' record were vital signs assessment (98.2%), fall risk assessment (93.3%), and intravenous fluid monitoring (92.2%), respectively. The least recorded practices stated by nurses were leisure activities assessment (53.1%), social support assessment (53.5%), and sexual function assessment (55.6%), respectively. Conclusion: It was determined that professional practices were not completely visible in the Nurse Observation Chart and other nursing records.